Modeling of force-displacement behavior of post-tensioned self-centering concrete connections. (1st November 2019) - Li, Lu-Xi; Li, Hong-Nan; Li, Chao; Yang, Yeong-Bin; Zhang, Cai-Yan
Highlights: A new analytical procedure for the force-displacement response of PTSC concrete connections is proposed. Values of the maximum concrete compressive strain are estimated. Possible deformation components throughout the loading process are incorporated. Abstract: This paper provides an analytical procedure for deriving the force-displacement relations of post-tensioned (PT) self-centering (SC) concrete connections. The restoring force of PT tendons is defined using the section analysis, in which direct estimation of maximum concrete compressive strain is incorporated instead of adopting the commonly used "monolithic beam analogy" method. Analytical models for the PTSC beam-column joints with and without energy dissipating devices are provided according to the force and deformation characteristics of each case. Using the validated finite element models, a parametric study including 100 PTSC connections is conducted with the ABAQUS platform to detect the variation pattern of maximum concrete strain and estimate its values for connections with different section dimensions, concrete strength and initial PT forces. The accuracy of proposed analytical models is verified based on comparisons with the finite element results and available experimental data.